2011
DOI: 10.1143/jjap.50.09mg01
|View full text |Cite
|
Sign up to set email alerts
|

One-Head Near-Field Writing/Erasing on a Rewritable Dual-Layer Optical Disk Having High-Index Cover and Separation Layers

Abstract: The method of Kittler and Falicov for binary alloys has been extended to the case when one of the components terminates the Bethe lattice. It has been applied to hydrogenated amorphous silicon (a-Si:H) and the results compared with experimental photo-emission spectra. It is shown that complex configurations such as SiH, and SiH, are responsible for some of the experimental peaks. This theory is compared with other meanfield theories and its limitations are fully discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Optical disc storage, by virtue of its inherent characteristics such as durability and disaster resistance, is suitable for satisfying the storage needs of enterprises. [2][3][4][5] Several technologies of realizing large-capacity optical storage have been reported, such as a volume holographic memory, [6][7][8][9] a solidimmersion objective lens system, [10][11][12] a multilayer disc system, [13][14][15] and others. [16][17][18][19][20][21][22] Multilayer technology for optical discs with a separated guide layer has been reported 23) as one of the most promising approaches for storing large-capacity data in a single disc.…”
Section: Introductionmentioning
confidence: 99%
“…Optical disc storage, by virtue of its inherent characteristics such as durability and disaster resistance, is suitable for satisfying the storage needs of enterprises. [2][3][4][5] Several technologies of realizing large-capacity optical storage have been reported, such as a volume holographic memory, [6][7][8][9] a solidimmersion objective lens system, [10][11][12] a multilayer disc system, [13][14][15] and others. [16][17][18][19][20][21][22] Multilayer technology for optical discs with a separated guide layer has been reported 23) as one of the most promising approaches for storing large-capacity data in a single disc.…”
Section: Introductionmentioning
confidence: 99%
“…A near-field optical recording (NFR) system using a solid immersion lens (SIL) 1) has a fourfold higher recording density than the Blu-ray disc system. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Some studies have shown the realization of a large recording capacity using multilayer recording techniques for optical disks, [17][18][19][20][21] but the data transfer rate is limited. The NFR system is expected to realize not only a large capacity but also a high data transfer rate because its numerical aperture (NA) is more than two times higher and the optical beam spot can be less than half the diameter of current Blu-ray optical systems.…”
Section: Introductionmentioning
confidence: 99%
“…The NFR system has more than four times higher recording density than the Blu-ray disc system. [2][3][4][5][6][7][8][9][10][11][12][13][14] Multilayer recording techniques for optical disks 15,16) is effective for realizing a large capacity, but the data transfer rate is limited as the mark size, which is caused by the numerical aperture (NA) of the 0.85-Blu-ray disc system. NFR techniques using SIL have more than two times higher NA than Blu-ray disc and have the feasibility of achieving more than two times higher data transfer rate recording at the same disk rotational speed; however, the feasibility of high-data-transfer-rate recording of more than 200 Mbps using NFR techniques with narrow-track pitch disks has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%